Arsenic record from a 3 m snow pit at Dome Argus, Antarctica. Issue 4 (18th March 2016) - Rong, Hua; Shugui, Hou; Yuansheng, Li; Hongxi, Pang; Mayewski, Paul; Sneed, Sharon; Chunlei, An; Handley, Michael
Abstract: This study presents an arsenic concentration time series from 1964–2009 at Dome Argus, Antarctica. The data show a very large increase in arsenic concentration from the mid-1980s to the late-1990s (by a factor of 22) compared with the values before the mid-1980s. This increase is likely to be related to the increased copper smelting in South America. Arsenic concentration then decreased in the late-1990s, most probably as a result of environmental regulations in South America. The sudden increase in arsenic concentration observed at Dome Argus coincides with similar increases observed at Dome Fuji and in Antarctica Ice Core-6 (IC-6) at the same time, suggesting that arsenic pollution during the period from the mid-1980s to the late-1990s was a regional phenomenon in Antarctica. Investigations of arsenic concentrations at these three Antarctic locations show that, during this time, regional arsenic distribution followed dust transport pathways associated with general climate models with South America as a major source region for the half of Antarctica facing the Atlantic and Indian oceans.